Nutritional Status of Under-Five Years’ Children in Pahari Caste Community of Nepal - Roy, Roshan Kumar; Poudel, Priyanka; Roy, Deepak Kumar; Karki, Supendra; Maharaj, Anuranjan; Bhandari, Keshav Raj; Mahato, Lalan Kumar (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Undernutrition remains a persistent public health challenge globally, particularly among marginalized populations such as the Pahari caste in Nepal. Understanding the multifactorial determinants of child nutrition is essential for developing effective, targeted interventions aligned with sustainable development goals. The objective of this study is to assess the nutritional status and associated determinants among under-five children in the Pahari community of Makwanpur District, Nepal. Method: A mixed-methods approach was employed. Quantitative data included anthropometric assessments (weight-for-age, height-for-age, and weight-for-height) and dietary surveys conducted among a representative sample of under-five children and their caregivers. Qualitative data were collected through in-depth interviews and focus group discussions to explore perceptions of nutrition, cultural norms, and barriers to optimal feeding practices. Result: Quantitative analysis revealed that 35% of children were stunted, 15% wasted, and 20% underweight. Qualitative findings indicated that poor nutritional outcomes were shaped by socio-economic hardship, traditional dietary practices, and limited awareness of child nutrition. Conclusion: Undernutrition among Pahari children is driven by a combination of socio-economic and cultural factors. Culturally sensitive, community-specific interventions are essential to improving child nutrition and health in marginalized populations.